Exploring the co-occurrence of depression and anxiety symptoms among Chinese vocational high school adolescents through a network approach - He, Yunhan; Yang, Danli; Liang, Kaixin; Zhang, Yunjia; Zhang, Hongchuan; Chi, Xinli (Frontiers in Psychology, 2025)
Depression and anxiety, prevalent among adolescents, show higher rates in females than males. However, little is known about symptom-level interactions and gender-specific network characteristics in secondary vocational students. This study adopted network analysis, including Gaussian graph models and directed acyclic graphs, to explore symptom-level relationships between depression and anxiety in secondary vocational students, identifying bridge and core symptoms, potential causation, and gender-specific network characteristics. Involving 7,471 students in a cross-sectional study, we utilized the Patient Health Questionnaire 8-item (PHQ-8) and Generalized Anxiety Disorders 7-item (GAD-7) for symptom measurement. Key findings include: bridge symptom was “sad mood (PHQ2).” Core symptoms were “fatigue (PHQ4),” “loss of control (GAD2),” “trouble relaxing (GAD4),” “sad mood (PHQ2),” “irritability (GAD6),” “excessive worry (GAD3),” and “feeling guilty (PHQ6).” There were numerous cross-disorder links between anxiety and depressive symptoms, predominantly from anxiety symptoms to depressive symptoms. “Irritability (GAD6)” was the initial symptom in the directed network. Females showed higher prevalence of depression and anxiety, and network global strength. This study firstly highlights the complex interplay between depressive and anxiety symptoms in secondary vocational students, with notable gender differences. The insights offer valuable guidance for developing targeted interventions and support strategies for this group.